Prototipo de bicicleta estática generadora de electricidad para centros deportivos: promoción de energías renovables y eficiencia energética - Ponce León, Andrés Alexander (Revista Científica, 2026)
This research seeks an educational alternative focused on promoting the use of renewable and non-conventional energy sources and good electricity consumption practices. To this end, a prototype of a stationary bicycle that generates electricity was designed and manufactured for use in sports centers. The prototype generates a maximum voltage of 12 volts. This voltage level allows for the power supply of small loads such as cell phone chargers and LED lighting. Surveys were used to measure the impact of this prototype, seeking to demonstrate users' interest in renewable energy and energy efficiency. The main result is that all users, after using this prototype, became interested in self-generation methods and in linking their physical effort with electricity production, which helped raise awareness about responsible energy use. The prototype stands out for its low cost, ease of use, and its ability to contribute to environmental and social well-being, making it a viable and environmentally friendly alternative for sports and recreational spaces. It also highlights the importance of this type of initiative in promoting sustainable practices and ecological awareness among users.